Evaluation of plasma and erythrocyte fatty acids C15:0, t-C16:1n-7 and C17:0 as biomarkers of dairy fat consumption in adolescents. (October 2019) - Slim, M.; Ha, C.; Vanstone, C.A.; Morin, S.N.; Rahme, E.; Weiler, H.A.
Highlights: Dairy intake increased in both intervention groups over a period of 12 months. At 12 mo, erythrocyte C15:0 increased in adolescents consuming ≥ 4 Dairy servings/d. At 12 mo, plasma C15:0 did not change in any of the study groups. Dairy intake positively correlated with erythrocyte C15:0 and C17:0 at 12 months. Abstract: Introduction: Pentadecanoic (C15:0), heptadecanoic (C17:0) and trans-palmitoleic ( t -C16:1n-7) fatty acids (FAs) are often used as biomarkers for dairy fat in adults. This study aimed to investigate the relationship between dairy product intake and these FAs in adolescents. Material and methods: Healthy adolescents were randomized to one of three groups (Group 1: control; Group 2: consume 3 dairy servings/day; and Group 3: consume ≥ 4 servings/d). C15:0, C17:0 and t -C16:1n-7 were quantified using gas chromatography. Dietary intakes were assessed by 24 h diet recalls. Results: No difference was observed in FAs at baseline or 6 months (mo), however, at 12 mo, erythrocyte C15:0 increased in group 3 (+0.37 µg/ml, p  = 0.01). Dairy intake increased in both intervention groups (Group 2: +1.4 servings/d; Group 3: +2.4 servings/d, p  < 0.0001) and positively correlated with erythrocyte C15:0 at 12 mo. Conclusion: Erythrocyte FAs appear to be associated with increasing dairy intakes during adolescence.